Ways to improve the results of surgical treatment of patients with multiple valve correction in combination with coronary pathology - R. M. Vitovsky; P. M. Semeniv; O. V. Kupchynskyi; V. F. Onishchenko; L. A. Klymenko (Ukrainian Journal of Cardiovascular Surgery, 2019)
Aim of the study. To determine the effect of surgical tactics on the duration of ischemic period with simultaneous combined correction of two or three valves of the heart and myocardial revascularizationMaterials and methods. The work is based on the analysis of the results of single-stage multivalve correction in conjunction with coronary artery bypass grafting in 93 patients, which was performed at the National Amosov Institute of Cardiovascular Surgery for the period from 2014 to 2016. Depending on the tactical approach and the sequence of surgical procedures, patients were divided into groups. 1 – “CABG off pump and subsequent correction of heart valves” (n = 15); 2 – “Correction of heart valves and bypass grafting in conditions of cardioplegia” (n = 78).Results. Using different approaches to achieve high-quality protection of the myocardium at the time of its ischemia, minimizing the impact of artificial circulation on the body by improving the conditions and reducing the ischemic heart time showed significant advantages of the method of pre-shunting CA in the working heart.Conclusions.1. Correction of combined multiple valve pathology with coronary heart disease requires prolonged cardiopulmonary bypass time and ischemic heart time, which requires reliable protection of the myocardium, which is difficult to carry out in the presence of stenoses in the lumen of the CA. 2. The use of the method of preventive restoration of coronary blood flow by bypassing the spacecraft on the working heart before clamping of the aorta, has significant advantages in the duration of the cardiopulmonary bypass time and ischemic time of the heart.